2006
DOI: 10.1007/bf02898441
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antenatal profile and immediate neonatal outcome in VLBW and ELBW babies

Abstract: Antenatal profile of preterm labour in our series showed a number of high risk factors. The identification of common high risk factors is important for appropriate prenatal care. A better neonatal survival rate was possible due to timely intervention, appropriate management and NICU care facility available in our tertiary care centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 20 publications
11
54
3
Order By: Relevance
“…In the present study, amongst maternal risk factors, anemia was the commonest (65%) followed by previous pre term delivery which was similar to the studies by Roy K K et al, 10 and Arvind Sehgal et al, 5 where the Anemia was commonest (32.6% and 65% respectively) maternal risk factor noted. 44% mothers did not receive adequate antenatal care (ANC) and babies born to them had unfavorable outcome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, amongst maternal risk factors, anemia was the commonest (65%) followed by previous pre term delivery which was similar to the studies by Roy K K et al, 10 and Arvind Sehgal et al, 5 where the Anemia was commonest (32.6% and 65% respectively) maternal risk factor noted. 44% mothers did not receive adequate antenatal care (ANC) and babies born to them had unfavorable outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Due to continued innovation in neonatal intensive care facilities during the last two decades, the survival of premature infants has significantly increased due to advancement in perinatal and neonatal treatment expertise and improvement in the care of high risk mother. 2 This increased survival rate in preterm babies is associated with increased morbidity and mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Male preponderance was seen with regard to NICU admissions as per studies done in other parts of India Sridhar et al and Roy et al 1,2,7 . But in our study, there was no significant difference between admissions and mortality pattern with regard to gender.…”
Section: Discussionmentioning
confidence: 56%
“…At the beginning of the third-trimester of pregnancy, the baby weighs about 1 kg, and most babies have the capacity to live outside the womb. 1 At this stage of pregnancy, the risk of stillbirth is about 2%, and the risk of death at the very beginning of life is only matched when people reach their 80s. [2][3][4][5] Once regular contractions have indicated that labour has begun, both the mother and her baby face a higher mortality risk than at any other stage of life.…”
Section: Why Stillbirths Mattermentioning
confidence: 99%